Io sono (come) voi! Alla ricerca della mobilitazione elettorale: leader e partiti populisti nell’Europa postcomunista - Soare, Sorina (SocietàMutamentoPolitica, 2017)
Populism has often been used to analyze political parties, leaders and post-communist movements. Most of the literature on this topic is concentrated on the ideological features of post-communist populism. Based on a comparison between the Slovak National Party, the Bulgarian Ataka and the Hungarian Jobbik, the analysis aims to provide new insights on the organizational dimensions of post-communist populist parties. More specifically, the analysis focuses on the features of the three parties’ leaders from their origins until 2016, and it is based on qualitative content analysis of official documents (party statutes and programs), as well as desk research. The paper argues that although highly centralized organizational structures and strong leaders characterize all of the three parties, important variances across cases can be documented. Differences are mainly explained in relation to the age of the parties analyzed and their origins. Beyond the limited empirical focus, the analysis fine-tunes the role of the party leader in post-communist political phenomena, the still open question being whether the parties analyzed look increasingly like mainstream parties when it comes to the features of their leaders, or the other way around.